Análisis termográfico en extremidades superiores de varones durante una tarea repetitiva a dos ritmos de trabajo: estudio experimental - López-Ontiveros, Miguel Ángel (2024)
The study analyzed the musculoskeletal behavior of five operators while performing a repetitive task at an experimental station to prevent workplace accidents and illnesses in the short, medium, and long term. It used infrared thermography to monitor temperatures, focusing on specific areas of the arm of the five workers. Workers showed greater muscle activity in the elbow, forearm, and shoulder at an average pace, with less impact on the hand and upper arm. When the pace increased, activity intensified in the hand, shoulder, and elbow, while it decreased in the forearm and upper arm. The results indicate that thermography helps identify levels of muscle activity, which could help prevent injuries. The study also showed that the operators increased their assembly production as follows: 1(+64), 2(+26), 3(+62), 4(+3), and 5(+52).